The Scale of Machiavellianism Strategies in its Second Modified Form "A field study on a sample of Tishreen University employees" - كحيلة, ريم; شيرين مرتكوش (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to identify the nature of Psychometric Properties of the modified Machiavellianism Strategies scale. Which was prepared by the researcher Martakoush (2020) in its initial form and then it was modified to became the scale in its final from of (72) items. It measure (6)strategies (Seize Opportunities,Honesty,Tolerance, Deception, Gossip and Caution).Each strategy has (12) items distributed into(3) areas (Relationship with the Manager and the Relationship between Colleagues) on a sample of (186) male and female employees at Tishreen University. In order to extract the psychometric properties of a scale. The indications of validity and reliability were checked using the validity of the arbitrators and consistency to verify the expressions of the scale. As for the stability,it was verified by repeating stability and stability using the Alpha-Cronbachs coefficient and the Split-Half stability coefficient.The results concluded thatthe values of validity and reliability coefficients were high and statistically significant and indicate the validity of the scale. The Machiavellian strategies were saturated with two factors, which together explained the total variance of the matrix. Keywords; Machiavellianism Strategies, Psychometric Properties,Tishreen University employees.